2003
DOI: 10.1627/jpi.46.148
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Interfacial-tension Predictions to Parachor-method Parameters

Abstract: The parachor method (PM) is widely used to predict interfacial tension (IFT) but may yield incorrect IFT values, and, thus, adjustment of the PM parameters may be necessary. The sensitivities of IFT predictions to the PM parameters were investigated by examining the Weinaug and Katz method (WKM) and the Lee and Chien method (LCM). Parameter adjustment of only the scaling exponent does not always yield good regression results, and including parachors (or related variables) in a set of regression parameters is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Most of the previous IFT models originated from the Parachor model. ,,, For example, Chalbaud et al developed a correlation on the basis of the Parachor model taking into account the influence of temperature, pressure, salt presence, and chemical structure of CO 2 . Ayirala and Rao proposed a new mechanistic Parachor model based on mass transfer to predict IFT in multicomponent hydrocarbon systems.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Most of the previous IFT models originated from the Parachor model. ,,, For example, Chalbaud et al developed a correlation on the basis of the Parachor model taking into account the influence of temperature, pressure, salt presence, and chemical structure of CO 2 . Ayirala and Rao proposed a new mechanistic Parachor model based on mass transfer to predict IFT in multicomponent hydrocarbon systems.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Comparison of the elemental composition and nuclear magnetic resonance (NMR) results of the two fractions indicates that ASIL had higher aromaticity (fa) and greater heteroatom (S, N, and O) content. The structural parameters calculated by Sato's method 13) suggested that ASIL had a slightly larger aromatic ring sizes, but shorter aliphatic chains than MaIL.…”
Section: Compositions Structural Characteristics Andmentioning
confidence: 98%
“…1 H-NMR and 13 C-NMR Spectroscopy 1 H-NMR and 13 C-NMR spectra were measured in CDCl3 with total mass spectra (TMS) as the internal standard using a Lambda 500 FT-NMR spectrometer at a proton resonance frequency of 600 MHz.…”
mentioning
confidence: 99%